Economic and ecological impacts associated with recreation on Colorado fourteeners - Lohman, Greta, author; Keske, Catherine, advisor; Kelly, Eugene Francis, committee member; Loomis, John B., committee member (Colorado State University. Libraries, 2010)
Research has shown that Colorado's 14ers (peaks reaching over 14,000 feet) are extremely popular hiking destinations, with estimates of over 500,000 people visiting the peaks each year. This study simultaneously explores the economic benefits that occur from the seasonal influx of visitors, and the associated costs to the environmental stability of these sensitive alpine areas. Through considering economic and environmental impacts together, this study creates a protocol to assess the environmental impacts on high recreation activity alpine areas such as 14ers. The study site is Quandary Peak, a 14er located just outside Breckenridge, CO. Findings from this study may be utilized by the Forest Service and other public lands management agencies and organizations to aid in establishing and refining recreational use policies. Economic results show that visitor expenditures and willingness to pay (WTP) values on 14ers are high compared to other nature-based recreation experiences. Additionally, expenditures and WTP values in 2006 compared to 2009 prove to be statistically similar, signifying that this industry is stable during times of a national economic downturn. These findings have positive implications for the economic strength and diversity potential for the surrounding rural communities. Data from this initial study also serves to address a methodological question of how the verbiage used in dichotomous choice WTP questions affects responses. Results indicate that asking questions specifically for an individual, verses a group, affects the WTP values. Correcting for this proves to be difficult, indicating that if researchers want individuals to answer on an individual basis this must be explicitly stated. To assess current environmental conditions, measurements were made in terms of soil compaction, vegetation cover, carbon and nitrogen content, bulk density and porosity, and soil erosion. Results show that environmental health is generally lowest for sites on trail and on trail margins, indicating that human traffic stresses the stability and health of these areas. Furthermore, impacts are not confined within trail parameters, suggesting potential over-use and congestion of the trails. The next stage of this study will be to assess the economic and environmental impacts of recreation on another 14er that has different visitation rates. Through such a comparison, a concept of carrying capacity can be developed to determine how increasing or decreasing levels of use influence the economic conditions of surrounding towns and the environmental conditions of the alpine peaks.
Keywords: willingness to pay; soil erosion; Fourteeners; contingent valuation; Colorado; alpine; Fourteeners (Mountains) -- Colorado; Mountaineering -- Environmental aspects -- Colorado; Mountaineering -- Economic aspects -- Colorado